Pengembangan Media Game Edukasi untuk Meningkatkan Kemampuan Calistung Aud di TK Telkom 1 Palembang: Penelitian - Azzahra Anggraini; Leny Marlina; Indah Dwi Sartika (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to develop an interactive educational game-based media application that is valid, practical, and effective in improving early childhood students’calistung (reading, writing, and counting) skills. The research was conducted at TK Telkom 1 Palembang with 26 children from Group B as subjects. This study used the ADDIE model (Analysis, Design, Development, Implementation, Evaluation) in the Research and Development (R&D) method. Data were collected through observation, questionnaires, and interviews and analyzed for validity, practicality, and effectiveness. The validation result showed content exprert scores of 87,06% and 100% language expert 88% and media expert 93,33%, categorized as very valid. The media practicality reached 92%, and effectiveness was confirmed by t-test results (|thitung|= 31,28 > ttabel = 2.009). Therefore, this interactive application can be used as an innovative and fun learning tool to enhance early childhood calistung skill.